2019
DOI: 10.1101/616672
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of DNA extraction methods on individual helminth egg and larval stages for whole genome sequencing

Abstract: Whole genome sequencing is being rapidly applied to the study of helminth genomes, including de novo genome assembly, population genetics, and diagnostic applications. Although late-stage juvenile and adult parasites typically produce sufficient DNA for molecular analyses, these parasitic stages are almost always inaccessible in the live host; immature life stages found in the environment for which samples can be collected non-invasively offer a potential alternative, however, these samples are typically yield… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“… 33 , 34 Additional refinements developed through SCORE studies and beyond now allow repeat analyses on unamplified genomic DNA, cost-effectively and without genome amplification bias, thereby improving data quality and giving the potential for greater analytical depth. 35 , 36 Such new methodologies and refinements allow an enormous reduction in the logistical effort required in assaying parasite populations. Furthermore, these methodologies can be applied to natural schistosome populations across continents, allowing wide-scale genetic and genomic analyses of schistosome populations over space and time, and encompasses all life stages from adult worms to free-living miracidia and cercariae (e.g., refs.…”
Section: Introductionmentioning
confidence: 99%
“… 33 , 34 Additional refinements developed through SCORE studies and beyond now allow repeat analyses on unamplified genomic DNA, cost-effectively and without genome amplification bias, thereby improving data quality and giving the potential for greater analytical depth. 35 , 36 Such new methodologies and refinements allow an enormous reduction in the logistical effort required in assaying parasite populations. Furthermore, these methodologies can be applied to natural schistosome populations across continents, allowing wide-scale genetic and genomic analyses of schistosome populations over space and time, and encompasses all life stages from adult worms to free-living miracidia and cercariae (e.g., refs.…”
Section: Introductionmentioning
confidence: 99%
“…Under controlled conditions, it would therefore be possible to access genetic material that is otherwise inaccessible in the unembryonated eggs present in patient or environmental samples. Indeed, we have shown that, while DNA can be recovered successfully from larval stages, this is not the case for eggs of certain species, which have a lower DNA content that is difficult to access through the eggshell [82]. Thus, by obtaining embryonated eggs and larvae, better parasite detection and diagnosis…”
Section: Mesocricetus Auratusmentioning
confidence: 99%
“…OPEN ACCESS using molecular techniques, and studies on genome variation in parasite populations via new high-throughput sequencing approaches, will be possible [82,83]. Surveillance of parasite populations using their genomic data has the potential to reveal signatures of demographic change or of recent selection due to anthelmintic drug use, and even detect the emergence of anthelmintic resistance [83].…”
Section: Trends In Parasitologymentioning
confidence: 99%
“…96% ethanol; Ayana et al, 2019 ) or on a solid substrate (e.g. FTA cards; Doyle et al, 2019a ), allowing greater flexibility of sampling, transport, and storage. Use across multiple drug classes : the FECRT can inform on drug resistance across all drug classes using a similar experimental format.…”
Section: Current Diagnostic Tools For Anthelmintic Resistance and Thmentioning
confidence: 99%
“…96% ethanol; Ayana et al, 2019 ) or on a solid substrate (e.g. FTA cards; Doyle et al, 2019a ), allowing greater flexibility of sampling, transport, and storage.…”
Section: Current Diagnostic Tools For Anthelmintic Resistance and Thmentioning
confidence: 99%